Implementasi Ren’py pada Game Visual Novel Tempat Bersejarah Kabupaten Demak - Arielaura Yulian Titanica; Febrian Wahyu Christanto; Aldian Umbu Tamu Ama; Rian Dwicahya Supriatman; Luffi Septian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
This research explores the use of games as a learning medium to enhance children’s knowledge of historical sites in Demak Regency. A survey of 50 junior high school students revealed that 13.3% were unaware of historical sites, while 80% had moderate awareness. To address this, an educational game in the visual novel genre was developed, presenting stories through images and interactive character dialogues. The game was developed using Ren’Py and the Multimedia Development Life Cycle (MDLC) method, which includes concept definition, design, material collection (characters, scenarios, animations, and audio), development, testing (Alpha and Beta), and distribution via Google Drive. The game aims to attract younger generations and encourage interest in learning history, particularly in Demak. Evaluation results show an average user satisfaction rate of 85%, categorized as “strongly agree.” This indicates that the visual novel-based educational game is an effective alternative learning medium for improving children’s knowledge of historical sites.